A Finite Element Analysis for the Damaged Rotating Composite Blade - Abdullah, Oday I. (Al-Khwarizmi Engineering Journal, 2019)
In this paper, the finite element method is used to study the dynamic behavior of the damaged rotating composite blade. Three dimensional, finite element programs were developed using a nine node laminated shell as a discretization element for the blade structure (the same element type is used for damaged and non-damaged structure). In this analysis the initial stress effect (geometric stiffness) and other rotational effects except the carioles acceleration effect are included.  The investigation covers the effect speed of rotation, aspect ratio, skew angle, pre-twist angle, radius to length, layer lamination and fiber orientation of composite blade. After modeling a non-damaged rotating composite blade, the work procedure was to apply different damage cases in reference to the non-damaged structure in order to compute the shift in the fundamental natural frequency and stresses. Damage occurs in several layers of the composite sheet in different locations throughout its volume, and through several layers of the sheet. The numerical results show a good agreement compared with the available investigations using other methods.